Automated GMP production and long-term experience in radiosynthesis of CB(1)tracer [F-18]FMPEP-d(2) - Salla Lahdenpohja; Thomas Keller; Sarita Forsback; Tapio Viljanen; Esa Kokkomäki; Riikka V. Kivelä; Jörgen Bergman; Olof Solin; Anna K. Kirjavainen (WILEY, 2022)
Here, we describe the development of an in-house-built device for the fully automated multistep synthesis of the cannabinoid CB(1)receptor imaging tracer (3R,5R)-5-(3-([F-18]fluoromethoxy-d(2))phenyl)-3-(((R)-1-phenylethyl)amino)-1-(4-(trifluoromethyl)phenyl)pyrrolidin-2-one ([F-18]FMPEP-d(2)), following good manufacturing practices. The device is interfaced to a HPLC and a sterile filtration unit in a clean room hot cell. The synthesis involves the nucleophilic(18)F-fluorination of an alkylating agent and its GC purification, the subsequent(18)F-fluoroalkylation of a precursor molecule, the semipreparative HPLC purification of the(18)F-fluoroalkylated product, and its formulation for injection. We have optimized the duration and temperature of the(18)F-fluoroalkylation reaction and addressed the radiochemical stability of the formulated product. During the past 5 years (2013-2018), we have performed a total of 149 syntheses for clinical use with a 90% success rate. The activity yield of the formulated product has been 1.0 +/- 0.4 GBq starting from 11 +/- 2 GBq and the molar activity 600 +/- 300 GBq/mu mol at the end of synthesis.